محاضرات في إدارة جودة الخدمات الصحية - محلب، فايزة (جامعة سطيف 1 فرحات عباس كلية العلوم الاقتصادية والتجارية وعلوم التسيير قسم علوم التسيير, 2026)
This pedagogical handbook aims to provide a comprehensive conceptual and practical framework for the management of healthcare service quality. It introduces students to the fundamental concepts related to quality, total quality management, and healthcare services, while emphasizing the specificities of quality implementation in healthcare institutions. The handbook addresses the stages of healthcare service quality management, including planning, control, assurance, evaluation, and continuous improvement, highlighting key measurement tools and quality assessment models. It also focuses on resource utilization and performance evaluation in healthcare organizations, stressing the importance of fostering a quality culture to enhance patient satisfaction, organizational performance, efficiency, and effectiveness. This handbook is intended for Master’s students in Health Economics and Hospital Management, with the objective of developing their ability to understand and apply healthcare quality management practices in real-world healthcare settings.
مطبوعة بيداغوجية موجهة لطلبة السنة الأولى ماستر، تخصص اقتصاد الصحة والإدارة الاستشفائية
تهدف هذه المطبوعة البيداغوجية إلى تقديم إطار مفاهيمي وتطبيقي شامل لإدارة جودة الخدمات الصحية، من خلال تعريف الطلبة بالمفاهيم الأساسية المرتبطة بالجودة، إدارة الجودة الشاملة، والخدمة الصحية، مع التركيز على خصوصيات تطبيق الجودة في المؤسسات الصحية. تتناول المطبوعة مراحل إدارة جودة الخدمة الصحية، بدءًا من التخطيط والضبط والضمان، وصولًا إلى التقييم والتحسين المستمر، مع إبراز أدوات القياس والنماذج المعتمدة في تقييم جودة الخدمات الصحية. كما تركز على استخدام الموارد وتقييم الأداء في المؤسسات الصحية، وأهمية تبني ثقافة الجودة لتحقيق رضا المستفيدين، تحسين الأداء، وتعزيز الكفاءة والفعالية. وتستهدف المطبوعة طلبة ماستر اقتصاد الصحة والإدارة الاستشفائية، بهدف تمكينهم من فهم آليات إدارة جودة الخدمات الصحية وتطبيقها عمليًا في السياق الصحي
Keywords: Healthcare Service Quality Management; Total Quality Management; Healthcare Services; Quality Assessment; Continuous Improvement; Healthcare Performance.; إدارة جودة الخدمات الصحية، الجودة الشاملة، الخدمة الصحية، تقييم الجودة، تحسين الجودة، أداء المؤسسة الصحية; Gestion de la qualité des services de santé; Qualité totale; Services de santé; Évaluation de la qualité; Amélioration continue; Performance hospitalière.